Effect of Environment and Genotype on the Protein Quality Attributes and Baking Characteristic of Newly Developed Wheat Inbred Lines - Noha İ. A. Mutwalı; Abdelmoniem İ. Mustafa; Elfadil E. Babıker; İsam A. Mohamed Ahmed (Journal of Agricultural Sciences)
The present work examined the effect of genotype and environment on protein content and fractions, gluten and starch fraction, SSL (sodium stearoyl-2-lactylate) and DMG (distilled mono glyceride) binding ability of starch and specific loaf volume (SLV) of six wheat genotypes grown in three different environment. Genotype and environment significantly affected all quality attributes under investigation. However, protein content and fractions showed differences in relative effects of genotype and environment. Most of the protein quality characteristics were influenced more by genotype than environment. Size distribution of gluten subunits was significantly affected by genotype and environment. It was observed that as the flour protein content increased, the magnitudes of monomeric proteins appeared to rise, but glutenin decreased. Flour protein content was expressively associated with gliadin and dough making characteristics. Environment influenced beedings.